Spinal cord injury patient quality of life, perspective and transformation: narrative review - Alonso Mayorga, Karen Andrea; Lora Ariza , Leonardo José (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2021)
Study design: Narrative review. Objective: To investigate the current panorama of knowledge associated with the quality of life of adult patients with spinal cord injury and its transformations in the last 10 years. Methods: A literature review was carried out in the main databases PubMed, Medline, PEDro, and Cochrane. The articles with the highest weight of evidence (systematic review and meta-analysis) were selected. Using the MeSH terms "Spinal Cord Injury AND Quality of Life" as search parameters. Additionally, grey literature articles were annexed to obtain epidemiological data and information in our environment. Results: Among the articles found, 33% dealt with psychological interventions, 25% with physical therapy interventions, 4% with telemedicine interventions, 4% with pre-hospital interventions, and 4% with the impact of initial rehabilitation interventions. In 12.5% of the articles, the patient's wishes regarding recovery were predominant, and 8% evaluated strategies that validated tools to quantify the improvement in quality of life in patients with spinal cord injury. Discussion: Patients with spinal cord injury present various complications associated with the disease, both physical and psychological. Multiple strategies have been addressed to improve the quality of life of these patients. It has been shown that interventions on the diseases associated with spinal cord injury have a positive impact on their quality of life. In turn, physical and psychological therapy becomes a pillar for the improvement of patients, however, there is no clarity on the appropriate therapeutic strategy in this regard, nor on the assessment tools for this problem. In turn, it is clear that the role of the environment is fundamental for the improvement of the individual, and that medicine can play an important role in improving the quality of life of patients with this entity. Conclusions: Spinal cord injury is a condition that generates an important affection on the quality of life of the patients who present it. Although several therapeutic methods have been demonstrated to achieve an improvement in it, there is still no clarity about the most effective methods, the best tools to face this type of patients or about the therapies that generate a greater and better impact.